2013
DOI: 10.5489/cuaj.768
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for optimization of surgical and pathological quality performance for radical prostatectomy in prostate cancer management: evidentiary base

Abstract: Background: The objective is to provide surgical and pathological guidelines for radical prostatectomy (RP) with or without concurrent pelvic lymph node dissection (PLND) to achieve optimal benefit for patients, with minimal risk of harm. Methods:For surgical questions, a literature search of MEDLINE, EMBASE and the Cochrane database was performed. A literature search for the pathological questions was not conducted since the protocol for invasive carcinomas of the prostate gland developed by the College of Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The positive margin rate (36%) in our study was similar to the population-based rate found in Ontario (which ranged from 0-53%). 11 It is difficult to compare these rates to studies that are not population-based, as there may be selection bias, however, the results are within the range of published series (18%-46%, with a mean of 31%) ( Table 2). A large population-based series from the Surveillance, Epidemiology and End Results (SEER) registry reported an overall margin positive rate of 21%.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The positive margin rate (36%) in our study was similar to the population-based rate found in Ontario (which ranged from 0-53%). 11 It is difficult to compare these rates to studies that are not population-based, as there may be selection bias, however, the results are within the range of published series (18%-46%, with a mean of 31%) ( Table 2). A large population-based series from the Surveillance, Epidemiology and End Results (SEER) registry reported an overall margin positive rate of 21%.…”
Section: Discussionmentioning
confidence: 64%
“…39 The positive margin rate for pT2 patients in our series (of 30 %) exceeded the 20% threshold held by most Ontario urologists. 11 However, the positive margin rates for pathologic T2 patients in British Columbia are generally comparable to the range of regional rates seen in Ontario (16%-42%), 11 although they are higher than those seen in other jurisdictions ( Table 2). The positive margin rate in British Columbia in pT3 cases (57%) are also comparable to the range of regional rates seen in Ontario (42%-83%), 11 and within the ranges of rates reported in the literature (24%-80%).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Only more recently, evidence accumulated that biochemical degradation of tissues can be observed within hours or even minutes after tissue excision. [13][14][15][16] Although recent work has focused on developing protocols/guidelines for better tissue manipulation and developing anti-degradation reagents such as RNA stabilizers and protease inhibitor cocktails, 3,[17][18][19][20] no degradation measurement tool exists currently.…”
mentioning
confidence: 99%